Behavior of Reinforced Concrete Hybrid Trapezoidal Box Girders Using Ordinary and Highly Strength Concrete (Journal of University of Babylon for Engineering Sciences, 2018)
In this paper, the general behavior of reinforced concrete hybrid box girders is studied by experimental and numerical investigation. Experimental work is included casting monolithically five specimens of box girders with trapezoidal cross section and testing it as simply supported under two point loading. Two specimens were cast as homogenous box girders (full normal strength concrete (NSC) (about 35 MPa) and full high strength concrete (HSC) (about 55 MPa)) and three specimens were cast as hybrid box girders (HSC in upper flange only, HSC in upper flange and half depth of webs, and HSC in bottom flange and total depth of webs). Experimental results showed significant effects of concrete hybridization on the structural behavior of box girders specimens such as: cracking loads, cracking patterns, ultimate strengths, and failure modes. The ultimate strength of Hybrid box girders increased by 23% as average when compared with the homogenous box girder (full NSC) and decreased by 9% as average when compared with homogenous box girder (full HSC). In numerical investigation, the tested specimens were modeled and analyzed using three dimensional non-linear finite element analysis. The analysis was carried out by using a computer program (ANSYS V16.1). The numerical results showed an acceptable agreement with the experimental work with difference about (3.12% and 9.588%) as average for ultimate load and deflection, respectively.